Synergistic Effects of Intranasally Administered GALR2 and Y1R Agonists on Cognitive and Mood-Related Behaviors in Adult Rats: Implications for Neurodegenerative and Mood Disorders - Moreno-Madrid, Isabel; Arrabal-Gómez, José Carlos; Serrano-Castro, Pedro; Díaz-Sánchez, Estela; Álvarez-Contino, José Erik; Barbancho-Fernández, Miguel Ángel; Sánchez-Pérez, José Andrés; Blanco-Reina, Encarnación; Fuxe, Kjell; Borroto Escuela, Dasiel Óscar; García-Casares, Natalia; Narváez-Peláez, Manuel (My University, 2024)
Abstract body: Background: The complexity of neurodegenerative and mood disorders necessitates innovative therapeutic strategies beyond current treatments. This study explores the combined therapeutic potential of Galanin receptor 2 (GALR2) and Neuropeptide Y Y1 receptor (Y1R) agonists, administered intranasally, on spatial memory, antidepressant-like behavior, and neurogenesis in adult rats. Methods: The investigation employed intranasal co-delivery of GALR2 agonist M1145 and Y1R agonist to adult rats, examining spatial memory through the object-in-place task and antidepressant-like effects via the Forced Swimming Test. Neuronal survival and differentiation were assessed by BrdU-IR profiles, doublecortin (DCX) labeling, and Proximity Ligation Assay (PLA) for GALR2/NPYY1R heteroreceptor complexes in the hippocampus. Results: Co-administration significantly improved spatial memory and exhibited antidepressant-like behaviors. Notably, the presence of GALR2/NPYY1R heteroreceptor complexes in the ventral hippocampal dentate gyrus was associated with these behavioral outcomes. Enhanced neuronal survival, increased proliferation of neuroblasts, and augmented DCX-positive cell numbers with mature dendritic morphology were observed, suggesting enhanced neurogenesis and neuronal differentiation. Conclusions: The synergistic action of GALR2 and Y1R agonists via intranasal delivery offers a promising therapeutic approach for improving cognitive function and mood, highlighting the potential for new treatment strategies in neurodegenerative and mood disorders. The critical role of GALR2 in these processes suggests a novel target for future pharmacological interventions.
Keywords: Sistema nervioso - Degeneración; GALR2 agonist; NPY1R agonist; spatial memory; antidepressant-like behavior; neurogenesis